METHODOLOGY AND MEANS FOR CIVIL ENGINEERING MONITORING - V. L. Solomakho; I. F. Miroshnichenko; P. A. Petrusenko (Наука и техника)
The paper considers tendencies for development of civil engineering monitoring. The main factors influencing on secure operation of the objects are specified in the paper. The general principles used for the development of civil engineering systems are investigated in the present paper. Their typical and structural scheme is proposed and classification of the applied technical means are cited in the given paper.